Masa Depan Kepemimpinan dalam Era Generative AI: Tantangan, Risiko, dan Peluang bagi Dunia Pendidikan dan Bisnis - Sindi Putri Habibah; Azziza Syifa Maharsi; Shintia Hijjah Nurhaliza; Mochammad Isa Anshori (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The rapid advancement of Generative Artificial Intelligence (AI) has brought fundamental changes to how organizations operate, particularly in leadership practices across education and business sectors. This transformation requires leaders not only to understand emerging technologies but also to effectively manage their strategic, ethical, and operational implications. This study aims to examine the future of leadership in the era of Generative AI by identifying the key challenges, risks, and opportunities that arise within modern organizational contexts. The research adopts an integrative literature review approach, synthesizing empirical and conceptual findings from reputable academic publications over the past five years. The analysis is conducted through a systematic selection of literature and thematic analysis to identify dominant patterns and trends in prior studies. The findings reveal that leadership in the era of Generative AI is shifting toward a more adaptive, collaborative, and data-driven model. Major challenges include technological complexity, limited digital competencies, and organizational resistance to change. The associated risks involve algorithmic bias, ethical concerns, as well as data security and privacy issues. Conversely, the opportunities include enhanced operational efficiency, accelerated innovation, and improved quality of data-driven decision-making. This study contributes by providing a conceptual synthesis that integrates leadership and technological perspectives, while offering practical implications for leaders in designing adaptive, ethical, and sustainable strategies to navigate AI-driven digital transformation.